A redox-responsive drug delivery system based on RGD containing peptide-capped mesoporous silica nanoparticles. Issue 1 (6th November 2014) - Li, Ze-Yong; Hu, Jing-Jing; Xu, Qi; Chen, Si; Jia, Hui-Zhen; Sun, Yun-Xia; Zhuo, Ren-Xi; Zhang, Xian-Zheng
Abstract : A smart drug delivery system, DOX@MSN-S-S-RGD, was constructed by anchoring the RGD containing peptides onto the surface of MSNs using disulfide bonds for enhanced tumor cellular uptake and subsequent efficient cell killing. Abstract : In this paper, an intracellular glutathione (GSH) responsive mesoporous silica nanoparticle (MSN-S-S-RGD) was developed as a drug nanocarrier by immobilizing the gatekeeper (RGD containing peptide) onto MSNs using disulfide bonds. The antitumor drug, DOX was loaded onto the porous structure of the MSNs and the DOX@MSN-S-S-RGD system has been proved to be an effective nanocarrier. It was determined that most of the drug could be entrapped with only a slight leakage. After being accumulated in tumor cells via the receptor-mediated endocytosis, the surface peptide layer of DOX@MSN-S-S-RGD was removed to trigger the release of the entrapped drug to kill the tumor cell due to the cleavage of the disulfide bonds by intracellular GSH.